Characterization of the contamination of the waters of the Villa Maria wetlands in the district of Nuevo Chimbote Ancash - Peru - Símpalo López, Wilson Daniel (2020)
The purpose of this research was to characterize the decontamination of the Villa María wetlands located in the city of Chimbote and to propose technologies to minimize their negative impact on the ecosystem of that locality. To this end, a physical-chemical and microbiological characterization of the water of these wetlands was carried out in two points, in order to determine the degree of contamination and thus propose solution alternatives using technologies that allow recover that ecosystem. The results of the tests at the first point (coordinates 09o 06' 23.7'' – 078-33' 06.8), were: total coliforms 1700 NMP/100ml; Thermotolerant coliforms 490 NMP/100ml; conductivity 17 980 uS/cm; biochemical oxygen demand 59 mg/l; chemical demand for oxygen 337 mg/l; dissolved oxygen 4.83 mg/l; pH 6.25 and salinity 16%. At point two (coordinates 09' 06' 34.4'' – 078- 32' 59.4'') the assays yielded the following results: total coliforms <1.8 NMP/100ml; thermotolerant coliforms <1.8 NMP/100ml; conductivity 196 000 uS/cm; biochemical oxygen demand 1 033 mg/l; chemical demand for oxygen 10 927 mg/l; dissolved oxygen 0.70 mg/l; pH 6.88 and salinity 20%. The results obtained from the different tests led to the completion of high pollution of the waters of these wetlands, so they propose the application of new technologies such as the use of ultrafine bubbles and biofilters for water decontamination, technologies that have already been applied in similar situations successfully.